TIG Welding Current Selection Based on Penetrant Test Results: Pemilihan Arus Las TIG Berdasarkan Hasil Uji Penetran - Mochammad Soliqudin; Prantasi Harmi Tjahjanti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Welding plays a crucial role in metal joining processes across construction and manufacturing industries. Specific Background Tungsten Inert Gas welding is widely used for aluminum components such as motorcycle rims due to its precision and quality. Knowledge Gap However, determining the optimal welding current to minimize surface defects remains a challenge. Aims This study aims to analyze the effect of current variation on TIG welding results using liquid penetrant testing. Results The findings show that lower current produces fewer defects, while higher current increases the occurrence of surface defects such as cracks and porosity. The optimal welding parameter is identified at 100A, which yields the best joint quality. Novelty This study highlights the integration of current variation analysis with penetrant testing for aluminum rim welding evaluation. Implications The results provide practical guidance for selecting welding parameters and improving early defect detection in aluminum welding processes. Keywords: TIG Welding, Aluminum Rims, Welding Current, Penetrant Testing, Welding Defects Key Findings Highlights Lower amperage produces minimal surface discontinuities Higher heat input correlates with defect formation Inspection method supports early quality verification